2005
DOI: 10.1002/rmv.477
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of influenza and associated illness in children aged 0-19 years: a systematic review

Abstract: A systematic review was conducted to estimate the incidence of influenza and concomitant morbidity and mortality in children from 0 to 19 years (0-19 years). Medline was searched for observational studies and placebo or non-treated arms of experimental studies providing occurrence rates of laboratory-proven influenza illness. From the 2758 titles identified, 356 full papers were reviewed based on the abstract or title; after searching their reference lists an additional 16 papers were found. Finally 28 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
4
28
0
2
Order By: Relevance
“…A systematic review of the incidence of influenza in people up to 19 years' old reported a seasonal variability of 0-46%; during a five year period the average incidence was 4.6% in this age group. During a period of 25 years the incidence was 9.5% in children under 5 6. Because of this variability and lack of carryover protection from one year's vaccine to the next,7 especially if the virus changes its antigenic configuration, single studies reporting data from one or two seasons are difficult to interpret.…”
Section: Which Evidence?mentioning
confidence: 99%
“…A systematic review of the incidence of influenza in people up to 19 years' old reported a seasonal variability of 0-46%; during a five year period the average incidence was 4.6% in this age group. During a period of 25 years the incidence was 9.5% in children under 5 6. Because of this variability and lack of carryover protection from one year's vaccine to the next,7 especially if the virus changes its antigenic configuration, single studies reporting data from one or two seasons are difficult to interpret.…”
Section: Which Evidence?mentioning
confidence: 99%
“…Based on these data, the average incidence, depending on age category, is between 5% and 9.5%. The clinical picture is usually described as mild [37]. Regarding the fluctuating incidence of ILI reported, it is likely that in adults, the average incidence does not exceed these figures.…”
Section: Human Influenzamentioning
confidence: 85%
“…However, symptomatic disease should preferably be corroborated by a positive laboratory test [36]. Only in children do such figures seem to be available for a considerable number of years [37]. Based on these data, the average incidence, depending on age category, is between 5% and 9.5%.…”
Section: Human Influenzamentioning
confidence: 97%
“…4 Een systematische review naar de incidentie van griep bij kinderen komt, bij de combinatie van door influenza veroorzaakte ziekte en bevestiging door laboratoriumonderzoek, tot een seizoensincidentie die uiteenloopt van 0 tot 48% van de populatie. 5 Als je het effect van de jaarlijkse griepvaccinatie op zijn waarde wilt beoordelen zul je echter met een gemiddelde incidentie moeten werken. Die gemiddelde incidentie per seizoen bedraagt bij kinderen van 0-5 jaar 9,5% en bij kinderen van 0-19 jaar 4,6%.…”
Section: Inleidingunclassified
“…Die gemiddelde incidentie per seizoen bedraagt bij kinderen van 0-5 jaar 9,5% en bij kinderen van 0-19 jaar 4,6%. [5][6][7] Directe en indirecte complicaties van griep kunnen zijn: longontstekingen, ontregeling en ernstiger ziekte bij preëxistente aandoeningen (decompensatio cordis, diabetes mellitus, astma) en met name bij 65-plussers een verhoogde kans op overlijden. In de meeste gevallen echter is influenza bij gezonde kinderen en volwassenen een ziektebeeld dat vanzelf weer overgaat.…”
Section: Inleidingunclassified